2019
DOI: 10.1016/j.abrep.2019.100181
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking, and hospital readmission among inpatients with psychiatric illness at an academic inpatient psychiatric facility, 2000–2015

Abstract: Introduction Smoking rates are up to 2–4 times higher among individuals with mental illness. Hospital readmissions for patients with psychiatric illness within a year of discharge are also high, and there is limited evidence of associations between smoking and these readmissions. Methods This study was a secondary data analysis using clinical data of psychiatric inpatients with initial admissions between the years 2000 and 2015. Following a descriptive analysis, logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A unique aspect of our study design, compared with prior retrospective studies, is the use of XGBoost and propensity score matching methods. With the development of machine learning algorithms, screening for critical risk factors that affect the disease course can be applied to medical diseases including psychiatric disease [20][21][22] . The XGBoost model achieves the best prediction modelling among the machine learning models and traditional regression models [23] .…”
Section: Discussionmentioning
confidence: 99%
“…A unique aspect of our study design, compared with prior retrospective studies, is the use of XGBoost and propensity score matching methods. With the development of machine learning algorithms, screening for critical risk factors that affect the disease course can be applied to medical diseases including psychiatric disease [20][21][22] . The XGBoost model achieves the best prediction modelling among the machine learning models and traditional regression models [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, psychiatric inpatients who smoked had a 33% increased chance of readmission within a year of discharge compared with never-smokers, which represented 5.1% excess annual psychiatric readmissions. 25 These differences were illustrated in a randomized trial conducted by Prochaska and colleagues who recruited people who smoked from psychiatric inpatient hospitals into a smoking cessation program. Program participants had a 2-fold lower risk of rehospitalization than those who did not participate in the program (OR = 0.52).…”
Section: Importance Of Treatmentmentioning
confidence: 99%
“…Therefore, it is incumbent on psychiatrists to address the outsized effect that smoking has on patients with mental illness. (Journal of Psychiatric Practice 2024;30; [23][24][25][26][27][28][29][30][31] KEY WORDS: smoking, mental illness, tobacco, psychiatry, public health…”
mentioning
confidence: 99%
“…In numerous research assessments, LOS in a psychiatric hospital for suicidal behavior was not related to the rate of suicide attempts, self-harm, or NSSI after hospital discharge or readmissions (Fontanella, 2008;Green and Worrall-Davies, 2008;Kagabo et al, 2017;Ougrin et al, 2013), although older studies reported that a longer LOS was associated with worse outcomes (Gold et al, 1993;Pfeiffer and Strzelecki, 1990). Regardless, Pottick (1995) is on the mark writing that insurance pressures have had the greatest impact on inpatient LOS for suicidality in youth.…”
Section: The Usual Inpatient Length Of Stay Is Too Short To Accomplis...mentioning
confidence: 99%